Pattern of refractive effort and actual willingness to pay for spectacles in patients visiting optical of tertiary hospitals in Kathmandu valley. - Shrestha,Junu (2019)
SUMMARY: Refractive error is the first cause of visual impairment and second cause of blindness in the world.18% of the total population in the world are visually impaired due to refractive error which can be improved with correction. The benefit package of Social Health Insurance in Nepal has provision of correction of refractive error with spectacles within one thousand rupees. In order to ensure the services being provided are well utilized by the patients, it is necessary to find out the most valued attributes and make provision of similar service, it can only be estimated from individual's willingness to pay. The purpose of the study was to determine the pattern of refractive error and actual willingness to pay for spectacles in patient visiting tertiary hospitals in Kathmandu Valley. The willingness to pay was measured by revealed preference method on the basis of hedonic regression. This study is descriptive cross sectional study with quantitative design. The study found, astigmatism as the most common type of refractive error (45.7%) followed by myopia (34.7%) among the total 567 study participants from 14 tertiary hospitals in Kathmandu valley. The age and level of education were significantly associated with the pattern of refractive error. Similarly, the history of spectacles wear, frequency of replacement and all five stated task demanding spectacles except reading and writing were significantly associated with refractive error. The average willingness to pay was NRs 1782. On multiple linear regression analysis of the willingness to pay and spectacles attributes, when socio-economic and demographic variables and spectacles wear attitude of the participants were adjusted, the β constant was 715.4. The adjusted β constant for log of willingness to pay from the multiple linear regression models was 6.80. The standardized β coefficient was highest for progressive lens type (β=0.397) followed by metal frame stainless steel (β=0.285) and so on. This study revealed that the provisioned amount in the benefit package only cover the cost of basic spectacles, basic spectacles with tinted lens and basic spectacle with bifocal lens type, which may not include the preferred attribute and may not ensure durability.